Development of Assessment Using Evidence-Centered Design (ECD) on Dynamic Fluids Material - Sidik Wijaya; Judyanto Sirait; Ray Cinthya Habellia (Universitas Lambung Mangkurat, 2025)
This research aims to develop an assessment using the Evidence-Centered Design (ECD) approach for dynamic fluid materials, employing the Research and Development (R&D) research method. This assessment research and development uses the ADDIE model, which was limited to the development stage to produce an assessment. The content validity test result for the questions, using Aiken's value, was 0.834, which is categorized as very high and valid. The data collection process in assessment development was carried out through validator input, assessment trial implementation, and student responses obtained through questionnaires as a basis for revision to produce a valid, reliable, and relevant instrument. Data were obtained through a limited trial with one student and a small-scale trial with one class of 12th-grade students using questionnaires. The results of the students' responses indicate that the Evidence-Centered Design (ECD)-based assessment is considered clear, relevant, and helpful for understanding concepts, although some questions were considered difficult. From this series of processes, a dynamic fluid assessment was produced as one alternative for teachers to measure student competency and develop evidence-based assessments.